2017
DOI: 10.1080/13543776.2017.1369958
|View full text |Cite
|
Sign up to set email alerts
|

Ectonucleotidase inhibitors: a patent review (2011-2016)

Abstract: Ectonucleotidases are a broad family of metallo-ectoenzymes that are responsible for hydrolysing a variety of nucleotides to nucleosides, hence orchestrating the activation of P1 and P2 cell receptors via controlled release of nucleotides and nucleosides. Many disorders such as impaired calcification including aortic calcification, neurological and immunological disorders, platelet aggregation, cell proliferation and metastasis. are characterized by an increase in expression of these ectonucleotidases. Consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…This simplified picture has prompted many pharmaceutical and biotechnology companies to develop a large number of reagents, small molecule drugs or antibodies, targeting the P2Rs most likely involved in inflammation and cancer, i.e., the P2X7R and the adenosine A2AR and A2BR (6,25,30). Along this same line of thinking, reagents targeting ecto-nucleotidases to slow down ATP hydrolysis and adenosine generation have also been developed (2).…”
Section: At Inflammatory Sites Atp Interacts With Other Proinflammatory Factorsmentioning
confidence: 99%
“…This simplified picture has prompted many pharmaceutical and biotechnology companies to develop a large number of reagents, small molecule drugs or antibodies, targeting the P2Rs most likely involved in inflammation and cancer, i.e., the P2X7R and the adenosine A2AR and A2BR (6,25,30). Along this same line of thinking, reagents targeting ecto-nucleotidases to slow down ATP hydrolysis and adenosine generation have also been developed (2).…”
Section: At Inflammatory Sites Atp Interacts With Other Proinflammatory Factorsmentioning
confidence: 99%
“…demonstrated that degradation of extracellular ATP or AMP by ectonucleotidases lead to the accumulation of deoxyATP, which prevent DNA synthesis by inhibiting ribonucleotide reductase ( 42 ). In subsequent experiments, inhibitors of CD39, CD38, and CD73 were added to reduce adenosine production and restore T cell proliferation ( 43 ). Damaged and stressed cells release NAD+, which are hydrolyzed in a stepwise manner to synthesize adenosine by CD38 and CD73 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies using a commercially available (APT102) engineered human nucleoside triphosphate diphosphhydrolase-3 (CD39L3) in a canine model of arterial thrombosis were very encouraging [126]. Conversely, various inhibitors of ectonucleotidases patented during the past few years [127], and the availability of therapeutic antibodies that selectively inhibit CD73 [128], widened the scope for modulating the CD39-adenosinergic axis in experimental therapeutics.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%